Vlijanie «effekta vozrasta» na otbor sportsmenov i komplektovanie sostavov molodežnych komand v igrovych vidach sporta - Bezmylov, N. (Science in Olympic Sport, 2017)
The paper addresses the issue of the «relative age effect» influence on the selection and multi-year training of young athletes that is currently relevant for many team sports. It is shown that trainers recruiting the members for junior and youth teams prefer children who were born in the first half of a calendar year and are more physically fit than their younger peers. This trend is completely absent in the adult sport world thus indicating a transient nature and the negative effects of those advantages that are achieved when the «relative age effect» is used in the process of competitive activity. There were a much larger number of players born in the first and second trimesters of a calendar year in the cadet and youth basketball teams of different age groups. This trend is maintained up to the level of high performance sport. Keywords: «relative age effect», biological age, selection of athletes, recruitment of members for teams, playing position, competitive activity.